2021
DOI: 10.1186/s13059-020-02249-z
|View full text |Cite
|
Sign up to set email alerts
|

N6-methyladenosine dynamics in neurodevelopment and aging, and its potential role in Alzheimer’s disease

Abstract: Background N6-methyladenosine (m6A) modification is known to impact many aspects of RNA metabolism, including mRNA stability and translation, and is highly prevalent in the brain. Results We show that m6A modification displays temporal and spatial dynamics during neurodevelopment and aging. Genes that are temporally differentially methylated are more prone to have mRNA expression changes and affect many pathways associated with nervous system devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
146
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(169 citation statements)
references
References 74 publications
8
146
2
Order By: Relevance
“…Transcriptome-wide sequencing of human and mouse brains showed that m 6 A modification is spatiotemporally regulated during neurodevelopment and aging ( Shafik et al, 2021 ). Increased m 6 A sites are observed as age increases.…”
Section: A In Neurological Disorders and Injuriesmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptome-wide sequencing of human and mouse brains showed that m 6 A modification is spatiotemporally regulated during neurodevelopment and aging ( Shafik et al, 2021 ). Increased m 6 A sites are observed as age increases.…”
Section: A In Neurological Disorders and Injuriesmentioning
confidence: 99%
“…Increased m 6 A sites are observed as age increases. The dynamically regulated m 6 A sites are enriched in alternatively untranslated regions of genes involved in aging-related pathways ( Shafik et al, 2021 ). Alzheimer’s disease (AD) is the most common form of dementia among elderly people ( Bateman et al, 2012 ).…”
Section: A In Neurological Disorders and Injuriesmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed further, studies in human populations and in mouse models have shown that specific dysregulations in m 6 A mRNA methylation contribute to AD pathogenesis. Typically, m 6 A levels in various brain regions increase with aging, and this disposition was shown to likely have relevance for AD development (Shafik et al, 2021). Interestingly, while METTL3 is downregulated in AD brain (hippocampus), it was observed to have accumulated in the postmortem AD brain at levels comparable to the insoluble Tau protein therein (Huang H. et al, 2020).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The formation of m 6 A is catalyzed by a methyltransferase complex (Methyltransferase-like 3, METTL3; methyltransferase-like 14, METTL14 and Wilms tumor 1-associated protein, WTAP) and erased by demethylases, including fat mass- and obesity-associated (FTO) protein and the α-ketoglutarate-dependent dioxygenase alkB homolog 5 (ALKBH5) protein ( Jia et al, 2011 ; Liu et al, 2014 ; Ping et al, 2014 ; Wang et al, 2016 ; Zheng et al, 2013 ). Emerging evidence indicates that aberrant m 6 A may be considered a new layer of epigenetic mechanisms underlying the pathogenesis of psychiatric diseases, such as cocaine addiction ( Hess et al, 2013 ), alcohol use disorder ( Bohnsack et al, 2019 ) and Alzheimer's disease ( Shafik et al, 2021 ). For major depressive disorder (MDD), a recent study demonstrated that the location and time of stress exposure alter m 6 A modifications ( Engel et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%